Dance and integration - Galiana Lloret, Vicenta (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2009)
Through this paper, we are reflecting on the consequences and the relationship established when people with functional diversity get in contact with an artistical activity such as dancing. We are dealing with different ways to tackle on this topic; in general terms, we are trying to understand and to assess the improvement in the quality of life that dancing can promote in people with functional diversity. In doing this, we want to analyse the topic in the other way round, that is, what this people with funtional diversity can give to the dancing business. This paper is the result of two years working and researching together with both the Complutense University of Madrid and the Dan Zass Association.
Keywords: Education through art; Dance; Functional diversity; Scenic Art; Integration; Normalization